In-hospital clinical outcomes after upper gastrointestinal surgery: Data from an international observational study. Issue 12 (December 2017) - Szakmany, T.; Ditai, J.; Kirov, M.; Protsenko, D.; Osinaike, B.; Venara, A.; Demartines, N.; Hubner, M.; Pearse, R.M.; Prowle, J.R.; ,
Abstract: Aims: Previous research suggests that patients undergoing upper gastrointestinal surgery are at high risk of poor postoperative outcomes. The aim of our study was to describe patient outcomes after elective upper gastrointestinal surgery at a global level. Methods: Prospective analysis of data collected during an international seven-day cohort study of 474 hospitals in 27 countries. Patients undergoing elective upper gastrointestinal surgery were recruited. Outcome measures were in-hospital complications and mortality at 30-days. Results are presented as n(%) and odds ratios with 95% confidence intervals. Results: 2139 patients were included, of whom 498 (23.2%) developed one or more postoperative complications, with 30 deaths (1.4%). Patients with complications had longer median hospital stay 11 (6–18) days vs. 5 (2–10) days. Infectious complications were most frequent, affecting 368 (17.2%) patients. 328 (15.3%) patients were admitted to critical care postoperatively, of whom 161 (49.1%) developed a complication with 14 deaths (4.3%). In a multivariable logistic regression model we identified age (OR 1.02 [1.01–1.03]), American Society of Anesthesiologists physical status III (OR 2.12 [1.44–3.16]) and IV (OR 3.23 [1.72–6.09]), surgery for cancer (OR 1.63 [1.27–2.11]), open procedure (OR 1.40 [1.10–1.78]), intermediate surgery (OR 1.75 [1.12–2.81]) and major surgery (OR 2.65 [1.72–4.23]) as independent risk factors for postoperative complications. Patients undergoing major surgery for upper gastrointestinal cancer experienced twice the rate of complications compared to those undergoing other procedures (224/578 patients [38.8%] versus 274/1561 patients [17.6%]). Conclusions: Complications and death are common after upper gastrointestinal surgery. Patients undergoing major surgery for cancer are at greatest risk.